Case Report: Aspergillosis and Cyathostoma americana co-infection in the lower respiratory tract of a Harris’s Hawk (Parabuteo unicinctus) - Rau, Susanne; Krone, Oliver; Schrödl, Wieland; Schinköthe, Jan (Frontiers in Veterinary Science, 2025)
A 12-year-old female Harris’s Hawk (Parabuteo unicinctus) that presented with prominent dyspnea and open-mouthed breathing with increasing respiratory problems during handling procedures died suddenly. Necropsy revealed extensive granulomatous airsacculitis, serositis, and pneumonia. Intralesional dark red helminths consistent with Syngamidae sp. were seen in the trachea, air sacs, lungs, and on top of multiple visceral organs. Furthermore, ascaridoid worms were found in the lumen of the small intestine. PCR analysis of both helminth species resulted in Cyathostoma americana and Porrocaecum moraveci, respectively. In addition, the air sacs contained innumerable areas of white to grayish sporulating mold. Mycological analysis revealed a prominent co-infection with Aspergillus fumigatus. While infection of the respiratory tract with Cyathostoma americana and air sac aspergillosis are known diseases in diverse raptor species, this case represents not only the first documented report of a Harris’s Hawk with pathological changes due to a prominent Cyathostoma americana infection but also of a raptor with Syngamidae-Aspergillus co-infection and concomitant endoparasitosis of the gut.